Relief in Aeolian Environment. The Surface of Nida Settlement - Pilkauskas, Mindaugas; Piličiauskas, Gytis; Vengalis, Rokas (Archaeologia Lituana, 2019)
During archaeological investigations in Nida settlement in 1974–1978, 2011–2013 and 2016 a lot of stratigraphic data from considerably wide area was gathered. Based on stratigraphy Neolithic paleosol of Nida settlement can be distinguished and it can be used as proxy for reconstruction of paleorelief. Paleosol was recorded in former depressions or on eastward slopes of former dunes. Large area in western part of the settlement was affected by aeolian processes where paleosol did not survive and in the eastern part former surface plunge deeply under groundwater level, these limited the territory considerably for paleorelief reconstruction. Analysis of the paleosol and stratigraphy displayed layering of artefacts in some parts of the settlement, which was interpreted as at least two periods of human activity. Also, in some parts of Nida very thick layer (> 1 m) with artefacts have been recorded which formed because of combination of anthropogenic activity and natural processes. An important insight is made about ancient topographic location of Nida settlement. Based on geological, botanical and geophysical data from Nida and other parts of Curonian spit we argue that earlier interpretation is not supported by recent data and we suggest that Nida settlement was in eastern part of the spit, on the shore of Curonian lagoon.